2010
DOI: 10.1186/1756-0500-3-286
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer in moroccan young women: a retrospective study

Abstract: BackgroundBreast cancer is uncommon in young women and induces more aggressive biologic characteristics. Survival in young women has been widely studied in developed countries. Less favorable prognosis and low survival were found.In Morocco, this study is the first investigation of clinical features, treatment and prognosis associated with breast cancer in young women.FindingsFour hundred and nine women aged 35 years or less were included in this study. All these women were diagnosed as having breast cancer at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…In the present study, we found that there was no difference in RFS between mastectomy and BCS+radiotherapy groups. This is consistent with a retrospective study of Moroccan young women by Abahssain et al [13]. Although the NCCN guidelines refer to age <35 years as a relative contraindication for BCS, BCS+radiotherapy seems to be a reasonable local treatment choice for early breast cancer in patients <35 years.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, we found that there was no difference in RFS between mastectomy and BCS+radiotherapy groups. This is consistent with a retrospective study of Moroccan young women by Abahssain et al [13]. Although the NCCN guidelines refer to age <35 years as a relative contraindication for BCS, BCS+radiotherapy seems to be a reasonable local treatment choice for early breast cancer in patients <35 years.…”
Section: Discussionsupporting
confidence: 90%
“…A number of factors may affect the survival rates in women with breast cancer, e.g. late presentation and diagnosis at an advanced stage, more aggressive tumours in young women (20,24,25), and hormonal, immunological and biological differences between younger and older women (26,27). This hormonal difference in young women may result in more rapidly growing tumour and thus reduced survival rates (26,28).…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer in young women is uncommon and very aggressive [ 2 ]. In the literature, there is not a wide definition of young women with breast cancer; sometimes they are defined as women under 35, sometimes women under 40 or 50 years [ 3 5 ]. In other publications, young women are attributed to all premenopausal women [ 6 ].…”
Section: Introductionmentioning
confidence: 99%